Pedagogic Competence of Teachers of State High School of Magelang City (Case Study On Certified And Non Certified Teachers At 1 and 2 State High School of Magelang City) - fifit firmadani; Molas Warsi (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
This study is intended to determine the implementation of pedagogic competence of teachers who are certified with non certified by conducting a case study in State and 2 Senior High Schools in Magelang. This research is planned to be carried out for six months. Specifically, this study aims to find out how the implementation of certified and non-certified teacher's pedagogic competence in State 1 and 2 Senior High Schools in Magelang city includes the ability to design learning, implement learning, evaluate learning.This research is a case study using a qualitative approach. Subjects were principals and deputy principals in the curriculum area of State 1 and 2 Senior High Schools in Magelang city, three certified teachers, three non-certified teachers and five students in State 1 and 2 Senior High Schools in Magelang. Data collection uses observation, interviews, and documentation as well as field logbooks. The analysis used in this study uses Milles Huberman data analysis technique which consists of three steps, namely data reduction, data display, and reflection drawing / verification. The targeted results of this study are descriptions of the implementation of certified and non-certified pedagogic teachers in SMA 1 and 2 in the city of Magelang; 2) scientific publications in scientific journals or national seminars.The results of the analysis show that teachers who have been certified with non-certification in State 1 and 2 Senior High Schools in Magelang City have the same level of pedagogical competence. This can be seen from the ability to design learning, implement learning, and evaluate learning. In both schools, both non-certified certification teachers have used interactive and innovative learning media, not yet fully utilizing technology in the learning process. Learning evaluation is done with daily assignments and tests